Keberadaan E. coli dalam Es Batu pada Jajanan Anak Sekolah Dasar - Anisa Nisviarisna; Mila Mardotillah; Tuti Surtimanah (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
Abstract: Existence of e.coli's pattern in ice cubes on paddler at primary school. E.coli is a large and diverse group of bacteria found in the human intestinal tract. Transmission of e.coli into a food product may be through fecal contamination due to lack of hand washing after defecation, additionally processed foods can be contaminated by e.coli from equipment that has not been cleaned and reused for the next food product one is ice cubes. This research aims to know the existence of and tracing the cause of e.coli in ice cubes on paddler at primary school in Subdistrict Antapani Bandung. Research carried out in 13 elementary school in Antapani 2018, is the type of qualitative research by conducting interviews to informant confirmed by laboratory test. Raw material for the manufacture of ice cubes using water of PDAM and water refill. This study stated that the water resources (SAB), trash and a work shirt is already 100% in state eligible, while only 70% to SPAL that use septic tank and 30% drain into the river, there are 10% that do the CTPS and 0% for the use of the APD. Observationally only dishcloth that reach 100%, the rest should be upgraded again. In terms of sanitation especially storage of ice cubes, there are 80% and 20% still do not qualify. Laboratory results state that all negative samples. Laboratory result that Ice cubes in producers and paddlers do not contain E. coli. Paddler is not yet eligible sanitation as a whole. Therefore, it is expected to pay more attention to cleanliness of the companionship.